Evaluating the Evolutionary Origins of Unexpected Character Distributions within the Bacterial Planctomycetes-Verrucomicrobia-Chlamydiae Superphylum - budd, aidan; Devos, Damien P. (Frontiers in Microbiology, 2012)
Recently, several characters that are absent from most bacteria, but which are found in many eukaryotes or archaea, have been identified within the bacterial Planctomycetes-Verrucomicrobia-Chlamydiae (PVC) superphylum. Hypotheses of the evolutionary history of such characters are commonly based on the inference of phylogenies of gene or protein families associated with the traits, estimated from multiple sequence alignments (MSAs). So far, studies of this kind have focused on the distribution of (i) two genes involved in the synthesis of sterol, (ii) tubulin genes, and (iii) c1 transfer genes. In most cases, these analyses have concluded that horizontal gene transfer (HGT) is likely to have played a role in shaping the taxonomic distribution of these gene families. In this article, we describe several issues with the inference of HGT from such analyses, in particular concerning the considerable uncertainty associated with our estimation of both gene family phylogenies (especially those containing ancient lineage divergences) and the Tree of Life (ToL), and the need for wider use and further development of explicit probabilistic models to compare hypotheses of vertical and horizontal genetic transmission. We suggest that data which is often taken as evidence for the occurrence of ancient HGT events may not be as convincing as is commonly described, and consideration of alternative theories is recommended. While focusing on analyses including PVCs, this discussion is also relevant for inferences of HGT involving other groups of organisms.